SOSIALISASI PENCATATAN SEDERHANA PENGELOLAAN UMKM PADA SANTRI PONDOK PESANTREN DARUSSALAM - Fitri, Syarifah Massuki; Syukri, Muhammad (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
Good financial record-keeping is one of the key factors for the successful management of micro, small, and medium enterprises (MSMEs). However, many MSMEs, particularly students (santri) at the Darussalam Islamic Boarding School who run small and medium enterprises, face various challenges in this regard. The primary issues include a lack of basic accounting knowledge, undocumented financial records, and limited access to resources. These challenges complicate business decision-making, such as determining selling prices, calculating profits, and planning for business expansion. This community service initiative aims to educate MSME students on financial management and record-keeping by providing solutions through the dissemination of simple financial management practices. The proposed approach includes basic accounting training and mentoring. By implementing these solutions, the team hopes that MSME students will better understand the importance of good financial management and be able to independently record and analyze their business finances. The results of this outreach program show that in a pre-test conducted with 20 students, only 4 individuals (20%) scored well. Following the dissemination of simple record-keeping education, the post-test results indicated significant improvement, with 18 students (90%) scoring well. This improvement in skills is expected to support the sustainability and growth of each business being operated.